Implementation challenges of Pradhan Mantri Jan Arogya Yojana: A Cross- Sectional study in Meerut, Uttar Pradesh - Verma, Niharika; Bano, Tanveer; Chopra, Harivansh; Singh, Ganesh; Mittal, Chhaya (Indian Journal of Community Health, 2022)
Background: Ayushman Bharat – Pradhan Mantri Jan Arogya Yojana has been launched to provide financial protection expenditure to nearly 500 million vulnerable Indians. For expanding the coverage under the scheme, it is necessary to understand the perspective of health care service providers involved in the scheme. Aim & Objective: To find out the bottlenecks in implementation of PMJAY scheme using empanelled hospitals’ perspective Settings and Design: Cross sectional study Methods and Material: 8 Public and 23 Private hospitals were selected through Simple Random Sampling from the list of PMJAY empanelled hospitals. The PMJAY Medical Officer co-ordinators in the empanelled hospitals were interviewed using a predesigned and pretested questionnaire. Statistical analysis used: Data was analysed using descriptive statistics in Epiinfo software. Results: Among the 31 empanelled hospitals studied, 93.5% were satisfied with the process for empanelment under PMJAY. 64.5% hospitals were not satisfied with the Health Benefit Packages. 77.4% hospitals perceived the PMJAY to be poorer as compared to private health insurance with reasons being poor grievance reprisal, poor claim processing and settlement, denial of reimbursement of health packages, poor rates of health packages and little information about the scheme. Conclusions: Various hurdles are being faced in the implementation of the scheme. There definitely remains a huge scope for further improvements so as to enhance the insurance coverage in the country.